Styles of volcano-induced deformation: numerical models of substratum flexure, spreading and extrusion - van Wyk de Vries, Benjamin; Matela, Ray (Journal of volcanology and geothermal research, 1998)
The gravitational deformation of volcanoes is largely controlled by ductile layers of substrata. Using numerical finite-element modelling we investigate the role of ductile layer thickness and viscosity on such deformation. To characterise the deformation we introduce two dimensionless ratios; Π a (volcano radius/ductile layer thickness) and Π b (viscosity of ductile substratum/failure strength of volcano). We find that the volcanic edifice spreads laterally when underlain by thin ductile layers ( Π a>1), while thicker ductile layers lead to inward flexure ( Π a<1). The deformation style is related to the switch from predominantly horizontal to vertical flow in the ductile layer with increasing thickness (increasing Π a). Structures produced by lateral spreading include concentric thrust belts around the volcano base and radial normal faulting in the cone itself. In contrast, flexure on thick ductile substrata leads to concentric normal faults around the base and compression in the cone. In addition, we show that lower viscosities in the ductile layer (low Π b) lead to faster rates of movement, and also affect the deformation style. Considering a thin ductile layer, if viscosity is high compared to the failure strength of the volcano (high Π b) then deformation is coupled and spreading is produced. However, if the viscosity is low (low Π b) substratum is effectively decoupled from the volcano and extrudes from underneath it. In this latter case evidence is likely to be found for basement compression, but corresponding spreading features in the volcano will be absent, as the cone is subject to a compressive stress regime similar to that produced by flexure. At volcanoes where basement extrusion is operating, high volcano stresses and outward substratum movement may combine to produce catastrophic sector collapse. An analysis of deformation features at a volcano can provide information about the type of basement below it, a useful tool for remote sensing and planetary geology. Also, knowledge of substratum geology can be used to predict styles of deformation operating at volcanoes, where features have not yet become well developed, or are obscured.